The Contribution of Al-Jabarti in Egyptian Historiography in the 19th Century - Riri Anggraini; Yuliana Nurfalina; Daniel Mahmud Chaniago (UIN Imam Bonjol Padang, 2024)
If we talk about Islamic Historiography, of course it refers to writing history in Arabic which has several periods such as Pre-Islamic Arabic Islamic Histiography, Early Islamic Historiography and Modern Islamic Historiography. The method that researchers use to explain this material is the library research method which is then strengthened by the Qualitative method which is Descriptive Analysis. This research aims to explain the development of Islamic Historiography which is marked by the period of Modern Islamic Historiography which is the peak of development for Islamic writing starting from the period of modern Islamic Historiography which was pioneered by a historian named Al-Jabarti who is also known as a figure of struggle and pioneer of the movement. Arab-Islamic revival in Egypt in the 19th century. The results of this research are that through his works in written form describing the state of Egypt which is very far behind the civilization of Western countries, Al-Jabarti was able to raise awareness and a sense of wanting to progress among the Egyptian people and they were willing to rise up to catch up with them. from various aspects of life such as politics, economics, education and other aspects.